2013
DOI: 10.1038/bjc.2013.422
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-β gene-modified human bone marrow mesenchymal stem cells attenuate hepatocellular carcinoma through inhibiting AKT/FOXO3a pathway

Abstract: Objective:This study aims to investigate the using of bone marrow mesenchymal stem cells (BMSCs) genetically engineered to produce interferon-β (IFN-β) as a gene delivery system to treat hepatocellular carcinoma (HCC) in vitro and in vivo.Methods:To measure the effects on tumour cell growth in vitro, IFN-β-producing BMSCs (BMSC/IFN-β) were co-cultured with the HCC cell line HepG2 and Huh7. Enzyme-linked immunosorbent assay (ELISA) was used to detect the IFN-β secretion in the BMSC culture condition medium (CM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 33 publications
2
32
0
Order By: Relevance
“…Of note, MSCs also have a tropism to inflammation sites and tumors [5]. This particular characteristic has driven the use of genetically engineered MSCs to deliver anti-cancer molecules directly to developing tumors [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, MSCs also have a tropism to inflammation sites and tumors [5]. This particular characteristic has driven the use of genetically engineered MSCs to deliver anti-cancer molecules directly to developing tumors [6].…”
Section: Discussionmentioning
confidence: 99%
“…hepatocytes) from apoptosis [4]. Furthermore, it has been postulated that BM-MSCs possess tropism to injury sites and tumors [5], which have justified their use as cellular vehicles for directly delivering anti-cancer drugs into tumors [6].…”
Section: Introductionmentioning
confidence: 99%
“…Activation of the Akt pathway has been contributed to increase tumor aggressiveness [18]. Xie et al [23] reported the association of suppression of Akt activity and enhanced transcriptional activity of FOXO3a in the cells treated with IFN-b. In consistence with previously identified significance of the Akt oncogenic kinase in HCC, our data indicate that Akt phosphorylation inhibited by IFNb is associated with reducing Akt activation.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that FOXO3a and Akt-regulated transcription factor have been found to be functionally important in the development of human HCC [20][21][22]. Xie et al [23] reported the association of suppression of Akt activity and enhanced transcriptional activity of FOXO3a in the cells treated with IFN-b. Thus, our data provide a line of evidence for the regulatory effect of IFN-b on Akt phosphorylation in HepG2 cells.…”
Section: Dose-dependent Activation Of Caspases 3 and 9 In Cells Treatmentioning
confidence: 99%
“…Xie et al [4] combined tumour necrosis factor α (TNF-α) and TNF-β and interferon (IFN-β) β and IFN-γ , and found that the in vitro migratory ability of MSCs was increased, but that the effect of migrating to the affected site was 'not sufficient to enhance wound repair'. In another study, Cheng et al [5] reported that MSCs with high expression of chemokine receptor 4 (CXCR4) administered via the tail vein after transfection homed to the ischaemic myocardium better than control cells did.…”
Section: Introductionmentioning
confidence: 99%